Association mapping by pooled sequencing identifies TOLL 11 as a protective factor against Plasmodium falciparum in Anopheles gambiae. (December 2015) - Redmond, Seth; Eiglmeier, Karin; Mitri, Christian; Markianos, Kyriacos; Guelbeogo, Wamdaogo; Gneme, Awa; Isaacs, Alison; Coulibaly, Boubacar; Brito-Fravallo, Emma; Maslen, Gareth; Mead, Daniel; Niare, Oumou; et al.
Abstract Background The genome-wide association study (GWAS) techniques that have been used for genetic mapping in other organisms have not been successfully applied to mosquitoes, which have genetic characteristics of high nucleotide diversity, low linkage disequilibrium, and complex population stratification that render population-based GWAS essentially unfeasible at realistic sample size and marker density. Methods We designed a novel mapping strategy for the mosquito system that combines the power of linkage mapping with the resolution afforded by genetic association. We established founder colonies from West Africa, controlled for diversity, linkage disequilibrium and population stratification. Colonies were challenged by feeding on the infectious stage of the human malaria parasite, Plasmodium falciparum, mosquitoes were phenotyped for parasite load, and DNA pools for phenotypically similar mosquitoes were Illumina sequenced. Phenotype-genotype mapping was carried out in two stages, coarse and fine. Results In the first mapping stage, pooled sequences were analysed genome-wide for intervals displaying relativereduction in diversity between phenotype pools, and candidate genomic loci were identified for influence upon parasite infection levels. In the second mapping stage, focused genotyping of SNPs from the first mapping stage was carried out in unpooled individual mosquitoes and replicates. The second stage confirmed significant SNPs in a locus encoding two Toll-family proteins. RNAi-mediated gene silencing and infection challenge revealed thatTOLL 11 protects mosquitoes againstP. falciparum infection. Conclusions We present an efficient and cost-effective method for genetic mapping using natural variation segregating in defined recentAnopheles founder colonies, and demonstrate its applicability for mapping in a complex non-model genome. This approach is a practical and preferred alternative to population-based GWAS for first-pass mapping of phenotypes inAnopheles . This design should facilitate mapping of other traits involved in physiology, epidemiology, and behaviour.